2004
DOI: 10.1353/cja.2004.0028
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Levels of Social Isolation and Loneliness among Older People in a Rural Area: A Twenty–Year Longitudinal Study

Abstract: The Bangor Longitudinal Study of Ageing (BLSA), conducted in rural Wales from 1979 to 1999, followed a cohort of survivors from more than 500 people over 20 years. Using both quantitative and qualitative data from the study, the factors associated with increases and decreases in loneliness and social isolation were identified. The study was based on a population sample and survivors were followed up every 4 years. From 1983 to 1987, 30 people aged 75 and over in 1979 were studied intensively. The customary mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
165
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(185 citation statements)
references
References 12 publications
18
165
1
1
Order By: Relevance
“…Similarly, higher levels of loneliness have been identified when aggregate measures or scales have been used compared with more "direct", self assessment measures (eg, asking people to rate the frequency of their loneliness on a scale from "always" to "never"). 29,30 In an analysis of data from UK and Australian research, Victor, Grenade and Boldy 29 found that although rates of "severe" loneliness were comparable for both types of measure used , the loneliness scale also revealed higher levels of "moderate" loneliness (assumed as broadly equivalent to "sometimes" lonely on the self-rating scale). This suggests that some older people may be more reluctant to admit directly to being lonely, unless it is quite obvious or severe.…”
Section: Community Settingsmentioning
confidence: 99%
“…Similarly, higher levels of loneliness have been identified when aggregate measures or scales have been used compared with more "direct", self assessment measures (eg, asking people to rate the frequency of their loneliness on a scale from "always" to "never"). 29,30 In an analysis of data from UK and Australian research, Victor, Grenade and Boldy 29 found that although rates of "severe" loneliness were comparable for both types of measure used , the loneliness scale also revealed higher levels of "moderate" loneliness (assumed as broadly equivalent to "sometimes" lonely on the self-rating scale). This suggests that some older people may be more reluctant to admit directly to being lonely, unless it is quite obvious or severe.…”
Section: Community Settingsmentioning
confidence: 99%
“…One of the principal reasons why social researchers devote so much attention to the social lives of older people is the concern that older people are at high risk of social isolation (Fahey and Murray, 1994 (Wenger and Burholt, 2003). As a subjective experience for older people, social isolation can be experienced as a relat;ve experience and can also be experienced with reference to others and to their earlier experiences.…”
Section: Social Isolationmentioning
confidence: 99%
“…Social isolation can increase with advancing age and this increase can be related to these same factors (Wenger and Burholt, 2003). Sensory acuity may diminish with old age, leading to limitations in the frequency and quality of social interactions (Saxon and Etton, 1987).…”
Section: Correlates Of Social Isolationmentioning
confidence: 99%
See 2 more Smart Citations